The Linguistic significances of the letter (if/ law): An analytical Jurisprudential study - Harb, Ahmad Helmi (Journal of Islamic Sciences, 2022)
This research handles (if/ law) letter, it is meanings letters that connect phrases which each other. There was great controversy around such letter in directing its significance; position and use. This was intended to show its meanings and scientific trends on its significance. Besides, extrapolation of Jurisprudential researches derived from its significance and methods of uses, which are established for jurisprudence Initiation Rules.The researcher herein depended on the descriptive methodology by reviewing the scientist statements and usage evidence of uses, in addition to analytical and comparative methodology in revealing the significant depth of (if/ law) uses, pursuant to scientific sayings and transmission evidences.The research concluded to assure (if/ law) significance on condition and emphasizing its indication on abstinence, in addition to the accuracy of more meanings indicated thereto; i.e. Release, investigate, reduce, wish, display, etcUpon reviewing the scientists' trends in directing (if/ law) significance, and the additional meanings where it is used, the research memorizes its effect in many Jurisprudential researches; i.e. Reasoning, concept, inference, release and else.
Keywords: Jurisprudence principles; significances; meanings' letters; conditional tools; (if/ law) letter